2021
DOI: 10.3390/cells10112838
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Responses of Pinna nobilis Individuals Enlightens the Etiology of Mass Mortality Situation in the Mediterranean Populations

Abstract: Due to the rapid decrease of Pinna nobilis populations during the previous decades, this bivalve species, endemic in the Mediterranean Sea, is characterized as ‘critically endangered’. In addition to human pressures, various pathogen infections have resulted in extended reduction, even population extinction. While Haplosporidium pinnae is characterized as one of the major causative agents, mass mortalities have also been attributed to Mycobacterium sp. and Vibrio spp. Due to limited knowledge concerning the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 64 publications
4
18
1
Order By: Relevance
“…Marteliosis or ‘’Aber disease’’ has been correlated with mortalities in Greek shellfish populations in the past in M. galloprovincialis and O. edulis [ 46 , 58 ]. However, disease etiology is considered complex in the concomitant presence of microorganisms and the ongoing rapid climate changes [ 59 , 60 ]. M. refringens dynamics in Mediterranean marine bivalve species are correlated with temperature rise [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marteliosis or ‘’Aber disease’’ has been correlated with mortalities in Greek shellfish populations in the past in M. galloprovincialis and O. edulis [ 46 , 58 ]. However, disease etiology is considered complex in the concomitant presence of microorganisms and the ongoing rapid climate changes [ 59 , 60 ]. M. refringens dynamics in Mediterranean marine bivalve species are correlated with temperature rise [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the multiplication and transmission of the parasite are triggered at temperatures above 17 °C, many studies have indicated that the parasite seems to be abundant at mature stages also when exposed to winter temperatures [ 61 , 62 , 63 ]. The presence of protozoan parasites and specifically M. refringens has been associated many times with down-regulation in the physiology and immune responses of marine bivalves [ 60 , 64 , 65 ]. Apart from the presence of pathogenic microorganisms that affect the physiology of the marine bivalves, abiotic factors also possess a key role in the physiology of the marine organisms [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…13,21,22 In particular, Pinna nobilis is now a critically endangered species with severe population declines resulting from mass mortalities associated with pathogens and the effect of climate change. 23,24 Aquaculture is an alternative to reduce adverse impacts on natural pen shell populations as it contributes to conservation and sustainable production while fostering social development by producing high-quality protein for rural areas. 25 Pen shells are suitable candidates for aquaculture given the large number of Atrina and Pinna species, their global distribution, high demand and fast growth rate (the fastest among bivalves).…”
Section: Introductionmentioning
confidence: 99%
“…The above has led to a drastic decline of wild populations of various Atrina and Pinna species over the past decades 13,21,22 . In particular, Pinna nobilis is now a critically endangered species with severe population declines resulting from mass mortalities associated with pathogens and the effect of climate change 23,24 …”
Section: Introductionmentioning
confidence: 99%
“…For instance, recently in Greece, Vibrio spp. decimated Pinna nobilis populations, with a synergistic effect on other microorganisms as well [14][15][16][17]. In this context, protozoan or protistan parasites, such as Marteilia refringens and Bonamia ostreae, respectively, have been detected during summer temperatures, causing heavy mortalities in flat oyster O. edulis populations, limitations due to lowering physiological functions, and also mortalities in cultured mussels, M. galloprovincialis, in Thermaikos gulf, Thessaloniki [18][19][20].…”
Section: Introductionmentioning
confidence: 99%